Via Láctea: História (parnasiana) de uma paixão - Simões Júnior, Alvaro Santos [UNESP] (My University, 2012)
Poesias (1888), Olavo Bilac’s first book, contains Via Láctea, a collection of sonnets of love that, in frank rupture with the romantic sentimentalism, is characterized by neoclassical moderation and contention. Universalizing treatment of the themes results in concealment of the particular circumstances in which the poems were composed. It is intended in these few pages to evidence the links between these texts and known episodes of the courtship of the poet and Amélia de Oliveira, the sister of Alberto de Oliveira, with the goal of providing an understanding of Via Láctea as a “love diary” in which the painful stations of a frustrated passion were registered.

Poesias (1888), livro de estreia do parnasiano Olavo Bilac, contém a Via Láctea, coleção de sonetos de temática amorosa que, em franca ruptura com o sentimentalismo romântico, caracteriza-se pela moderação e contenção neoclássicas. O tratamento universalizante dos temas acaba por ocultar as circunstâncias particulares em que foram compostos os poemas. Pretendese, nestas poucas páginas, evidenciar os vínculos desses textos com episódios conhecidos do namoro do poeta com Amélia de Oliveira, irmã de Alberto de Oliveira, com o objetivo de propiciar a compreensão da Via Láctea como um “diário amoroso” em que ficaram registradas, à maneira parnasiana, as dolorosas estações de uma paixão malograda.
Via Láctea (1888): story of a passion
Keywords: Olavo Bilac; Poesias; Via Láctea; Sonnet; Olavo Bilac; Poesias; Via Láctea; Soneto